Unilateral Sweating: A Case Study of Localized Unilateral Hyperhidrosis - Zubin Vaid (Wolters Kluwer Medknow Publications, 2024)
Localized unilateral hyperhidrosis (LUH) is a rare disorder with intense sweating in a specific area, often without common triggers. This study details a 32-year-old man with activity-induced unilateral sweating. Comprehensive tests ruled out serious conditions. This unique case adds to the limited reports of LUH in healthy individuals.